2014
DOI: 10.3855/jidc.3510
|View full text |Cite
|
Sign up to set email alerts
|

Human brucellosis in Turkey: different clinical presentations

Abstract: Introduction: Brucellosis is still endemic in Turkey and presents a major public health risk. The aim of this study wasto investigate the clinical and laboratory properties and complications of brucellosis cases. Methodology: The files of 370 patients (162 males, 208 females) with brucellosis between March 2006 and January 2012 were analyzed retrospectively. Results: The mean age of patients was 39, 6±18.2 years. The major risk factor was unpasteurized dairy products in 155 (41.8%) cases. The complications inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
7
35
2
7
Order By: Relevance
“…In spite of its low incidence, brucellosis endocarditis accounts for the majority of brucellosis-related deaths (4). The low ratio of endocarditis in this study (1.2%), was in agreement with previous studies (12,21,22). Abdi-liae et al (11) and Namidura et al (23) reported brucellosis endocarditis in 3.5% and 6.8% of their cases, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In spite of its low incidence, brucellosis endocarditis accounts for the majority of brucellosis-related deaths (4). The low ratio of endocarditis in this study (1.2%), was in agreement with previous studies (12,21,22). Abdi-liae et al (11) and Namidura et al (23) reported brucellosis endocarditis in 3.5% and 6.8% of their cases, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Anemia, leukopenia, thrombocytopenia, leukocytosis, thrombocytosis, and elevated ESR were detected in patients with brucellosis in previous studies (12,16,21,24). Anemia, which was found in 44 (53%) patients, was found as the most common hematological abnormality in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…enfeksiyonları, insidansında hafi f a bir düşme görülmekle birlikte, ülkemizde halen endemik olarak bulunmaktadır 7,10,11 . Bruselloz birçok organ ve sistemi etkileyebilen sistemik bir hastalık olup, akut, subakut ve kronik olmak üzere üç formda görülmektedir 7,10 . Klinik tablo; asemptomatik enfeksiyondan ateş, gece terlemesi ve eklem ağrılarının olduğu tipik görünüme kadar değişebilir 7 .…”
Section: Discussionunclassified
“…Bruselloz birçok organ ve sistemi etkileyebilen sistemik bir hastalık olup, akut, subakut ve kronik olmak üzere üç formda görülmektedir 7,10 . Klinik tablo; asemptomatik enfeksiyondan ateş, gece terlemesi ve eklem ağrılarının olduğu tipik görünüme kadar değişebilir 7 . Hematolojik komplikasyonlar brusellozda sık görülmekte ve birçok hematolojik hastalığı taklit edebilmektedir [11][12][13] .…”
Section: Discussionunclassified
See 1 more Smart Citation